ChemInform Abstract: tert‐Butyl Sulfoxides: Key Precursors for Palladium‐Catalyzed Arylation of Sulfenate Salts. Issue 44 (15th October 2015) - Gelat, Fabien; Lohier, Jean‐Francois; Gaumont, Annie‐Claude; Perrio, Stephane
Abstract Sulfenate salts, generated in situ by pyrolysis of tert‐butyl sulfoxides in the presence of K3PO4 undergo Pd‐catalyzed cross‐coupling reaction with aryl iodides, bromides, and triflates to give aryl sulfoxides.